Implementation of realistic mathematic education (RME) learning model in improving critical thinking skills - Susandi, Ardi Dwi; Widyawati, Santi (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Learning mathematics that can improve elementary school students' critical thinking skills is rarely done. Therefore, students' mathematical necessary thinking skills still need to improve. The realistic Mathematics Education (RME) learning model is expected to enhance mathematical critical thinking skills because of providing contextual problems to students. This study aims to determine the effect of the Realistic Mathematics Education (RME) learning model on students' critical thinking skills in mathematics. This research uses quasi-experimental research. The population in this study were students of class VI SDN 1 Kalikoa, Cirebon Regency. The sample selection in this study was carried out using a cluster random sampling technique to determine the experimental and control classes. In this case, two classes were selected: class VI A as the practical class and class VI B as the control class. The instrument for collecting data tests mathematical critical thinking skills on integer material. The results showed that the RME learning model is more effective than the direct learning model on students' critical thinking skills in mathematics. This is because the value of , and   at a significance level of 5% and DK of 40, which means , so H0 was rejected, and H1 was accepted. The results of this study can be used as input for teachers and prospective teachers to improve themselves concerning the teaching that has been done and the student's critical thinking skills that have been achieved by paying attention to the right learning model to improve students' critical thinking skills in mathematics.